2004
DOI: 10.1074/jbc.m310284200
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor γ Induces a Phenotypic Switch from Activated to Quiescent Hepatic Stellate Cells

Abstract: Depletion of peroxisome proliferator-activated receptor ␥ (PPAR␥) accompanies myofibroblastic transdifferentiation of hepatic stellate cells (HSC), the primary cellular event underlying liver fibrogenesis. The treatment of activated HSC in vitro or in vivo with synthetic PPAR␥ ligands suppresses the fibrogenic activity of HSC. However, it is uncertain whether PPAR␥ is indeed a molecular target of this effect, because the ligands are also known to have receptor-independent actions. To test this question, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
253
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(274 citation statements)
references
References 41 publications
(52 reference statements)
14
253
1
6
Order By: Relevance
“…[4][5][6]10,[23][24][25] JunD is also the major Jun family protein expressed in activated pancreatic stellate cells, indicating a generic role for JunD in fibrogenesis. 26 Studies with junD Ϫ/Ϫ mice and cells have revealed new physiological functions of JunD, including regulation of spermatogenesis, control of cell senescence and apoptosis, prevention of renal cell proliferation and hyperplasia, regulation of lymphocyte proliferation and differentiation, inhibition of tumor angiogenesis, and cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]10,[23][24][25] JunD is also the major Jun family protein expressed in activated pancreatic stellate cells, indicating a generic role for JunD in fibrogenesis. 26 Studies with junD Ϫ/Ϫ mice and cells have revealed new physiological functions of JunD, including regulation of spermatogenesis, control of cell senescence and apoptosis, prevention of renal cell proliferation and hyperplasia, regulation of lymphocyte proliferation and differentiation, inhibition of tumor angiogenesis, and cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…52 On the other hand, treatment of the activated HSCs with an adipocyte differentiation cocktail or ectopic expression of PPAR␥ or SREBP-1c causes their reversal to the quiescent phenotype. 53,54 Of the known adipogenic transcription factors, PPAR␥ has been investigated extensively. The expression of PPAR␥ is reduced in activated HSCs which can be restored with PPAR␥ ligands.…”
Section: B3 Reverse Transdifferentiation Of Activated Hscs To Quiescmentioning
confidence: 99%
“…52 Furthermore, by using adenoviral vector to ectopically express PPAR␥ in cultureactivated HSCs, researchers have demonstrated expression of PPAR␥ can restore the morphological and biochemical characteristics of quiescent HSCs, including accumulation of vitamin A. 53 This reversal was associated with decreased binding of JunD to the AP-1 site. These findings suggest a possibility that PPAR␥ and other adipogenic factors may serve as important therapeutic targets for liver fibrosis.…”
Section: B3 Reverse Transdifferentiation Of Activated Hscs To Quiescmentioning
confidence: 99%
“…The PPARδ isoform (also known as PPARβ) contributes to the regulation of glucose and lipid metabolism while exerting anti‐inflammatory properties in the liver by skewing M2 polarization of Küpffer cells 9, 10, 11. PPARγ and PPARδ are expressed at various levels in hepatic stellate cells (HSCs), a driver of liver fibrosis; PPARγ is key in keeping HSCs in a quiescent nonfibrogenic state 12, 13…”
Section: Introductionmentioning
confidence: 99%